Análise das propriedades físicas em estrutura do tecido ósseo de eqüinos - Nogueira Filho, Paulo de Tarso Vianna [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
This project has several objectives: To determine medium values and variations of the density, porosity, humidity, shrinkage volume and the coefficient of mass attenuation of gamma radiation of 59,6 keV of the radioisotope 241Am, using samples of equine radio, in growth and adult. The samples of bones were supplied by the Department of Pathology of University of Veterinary Medicine and Zootechnics - UNESP campus Botucatu. Bones of the paws front left of two males were used. Of each bone ten samples were removed. Those samples were prepared to just obtain compact bony fabric, being submitted to the rehearsal of determination of the density by the immersion method in water and determination of the coefficient attenuation lineal for the method of attenuation of the radiation of the 241Am, also obtaining your humidity content. Still, they were obtained new samples starting from the ground samples and verified the density of the particles present in that, obtaining the medium value of the coefficient of mass attenuation. The results showed the medium values and significant statistical variations of the density, porosity, humidity, shrinkage volume and coefficient of mass attenuation of gamma radiation of 59, 6 keV of the radioisotope 241Am in the samples, establishing some relationships between of the certain physical parameters with biological aspects and possible existent influences between them

Este projeto tem vários objetivos: Determinar valores médios e variações da densidade, porosidade, umidade, retratibilidade volumétrica e do coeficiente de atenuação de massa da radiação gama de 59,6 keV do radioisótopo 241Am, utilizando amostras de rádio eqüino, em crescimento e adulto. As amostras de ossos foram fornecidas pelo Departamento de Patologia da Faculdade de Medicina Veterinária e Zootecnia - UNESP campus Botucatu. Foram utilizados ossos das patas dianteiras esquerda de dois machos. De cada osso foram retiradas dez amostras. Essas amostras foram preparadas para obter apenas tecido ósseo compacto, sendo submetidas ao ensaio de determinação da densidade pelo método de imersão em água e determinação do coeficiente de atenuação linear pelo método de atenuação da radiação do 241Am, obtendo também seu teor de umidade. Ainda, foram obtidas novas amostras a partir das amostras moídas e verificada a densidade das partículas presente nas amostras, obtendo o valor médio do coeficiente de atenuação de massa. Os resultados mostraram os valores médios e variações estatisticamente significativas da densidade, porosidade, umidade, retratibilidade volumétrica e coeficiente de atenuação de massa da radiação gama de 59,6 keV do radioisótopo 241Am nas amostras, estabelecendo algumas relações dos parâmetros físicos determinados com aspectos biológicos e possíveis influências existentes entre eles
Keywords: Fisica medica; Equino - Diagnóstico; Densidade óssea; Método de imersão; Coefficient of mass; Immersion method